Simulation of grid connected PV system with PI, fuzzy-GA based controllers for power flow control - Malladi Lakshmi Swarupa; Kamasamud Sree Latha; Dakka Obulesu (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Nowadays, renewable energy sources turned into a choice to fulfill the expanding load need since they are ecological inviting and furthermore accessible bountiful in nature. Due to the easy availability of solar-powered vitality, the photovoltaic (PV) system is gaining popularity as a renewable energy option. Most of the energy from a PV array may be dissipated by using the maximum power point tracking (MPPT) method. The force quality problems, the real and responsive force stream problems, are a major concern when transferring a mass measure of intensity from a PV array to the power grid. This research proposes a unique control technique for regulating the power flow and resolving power quality concerns brought on by the integration of PV arrays into an existing power infrastructure. For effective management of real and receptive force stream in matrix related photovoltaic framework, it includes a PI-GA, fuzzy-GA based flowed regulator dealt with adaptable AC transmission framework gadget, specifically static synchronous compensator (STATCOM). As a result, the fuzzy rationale regulator creates a control vector, which is in this way tweaked utilizing a standard calculation.